Answer:
Step-by-step explanation:
x + y + z = 97 eq1
x - z = 9 eq2
y = 2z eq3
Since y is already defined in eq3, we can substitute eq3 into eq1.
x + 2z + z = 97
x + 3z = 97 new eq1
Now, we have only 2 equations to work with that have two variables.
x + 3z = 97 new eq1
x - z = 9 eq2
Subtract eq2 from new eq1 to eliminate the x terms.
4z = 88
z = 22
Next, substitute this value of z into eq3 to solve for y.
y = 2(22)
y = 44
Finally, we can substitute the values of y and z into eq1 to solve for x.
x = 97 - 44 - 22
x = 31
The three numbers are 22, 31, and 44.